Can Digital Human Capital Mitigate CO2 Emissions? Empirical Test for Post-Communist Countries - Djalilov, Bekhzod; Kobiljonov, Islomjon; Salahodjaev, Raufhon (International Journal of Energy Economics and Policy, 2023)
This study investigates the relationship between internet users, a proxy for digital human capital, and CO2 emissions in a sample of Post-Communist countries over the period 1990-2019. The results suggest that internet diffusion is negatively and significantly correlated with CO2 emission even after controlling for other economic antecedents of environmental degradation. Moreover, using fixed effects two-stage least squares estimator, we document that internet has causal impact on carbon emissions. In the full specification, a 10 percentage points increase in internet use leads to 4.2% decrease in CO2 emissions across Post-Communist countries. These results remain intact even when we introduce additional control variables in the model and conduct analysis on sub-samples. The papers highlights that human capital leads to sustainable development in developing countries.